2021
DOI: 10.1108/ijaim-11-2020-0186
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance practices and firm performance: a configurational analysis across corporate life cycles

Abstract: Purpose This study aims to explore corporate governance (CG) practices that can lead to firms’ better performance in different organizational life cycles. The authors propose a configurational approach to explore how a set of CG practices combine in bundles to achieve high performance outcomes for firms across their corporate life cycles. Design/methodology/approach Fuzzy-set qualitative comparative analysis was used to analyze a sample of data of 21 countries and 9 industries. Data referred to the period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
0
7
0
3
Order By: Relevance
“…The initial sample comprised of a total of 2,954 firms. We excluded financial firms and real estate industries, consistent with previous literature (Amin et al , 2021; Ayedh et al , 2019; Šušak, 2020; Liu and Sun, 2022), because of their distinctive accounting policies and business activities, resulting in a sample of 2,322 firms. Finally, firms with insufficient data required, along with firms with less than 15 observations in the year-industry group, were dropped because of data unavailability, resulting in a sample of 2,036 firms.…”
Section: Methodsmentioning
confidence: 99%
“…The initial sample comprised of a total of 2,954 firms. We excluded financial firms and real estate industries, consistent with previous literature (Amin et al , 2021; Ayedh et al , 2019; Šušak, 2020; Liu and Sun, 2022), because of their distinctive accounting policies and business activities, resulting in a sample of 2,322 firms. Finally, firms with insufficient data required, along with firms with less than 15 observations in the year-industry group, were dropped because of data unavailability, resulting in a sample of 2,036 firms.…”
Section: Methodsmentioning
confidence: 99%
“…Studies indicate that gender-diverse boards attribute to fewer malpractices (Nekhili & Gatfaoui, 2013). Empirical evidence points towards an association between board diversity and corporate performance (Al-Jaifi, 2020; Amin et al, 2021; Dang & Nguyen, 2021; Gordini & Rancati, 2017; Martinez & Rambaudm, 2019). The organisation’s performance is also affected by its characteristics of the organisation (Abdullah et al, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to the findings of Ying et al (2021) , audit committees that have entirely independent members and at least one member with prior expertise in accounting or a related field have a negative correlation with financial restatements. Research conducted by Amin et al (2021) found that businesses that engage in fraudulent activity are more likely to have less independent audit committees.…”
Section: Hypotheses Developmentmentioning
confidence: 99%